1996
DOI: 10.1159/000127150
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Influence Basal and Stress-Modulated Hypothalamic-Pituitary-Thyroidal Function in Fischer 344/N Rats

Abstract: To investigate possible gender- and age-associated changes of the hypothalamic-pituitary-thyroid (HPT) axis at baseline and during stress, we studied healthy young (3-month) and old (23-month) female 344/N Fischer rats at the basal state and after 2 h of immobilization (IMMO), in parallel to age-matched male rats. At baseline, there were no major differences of HPT axis functions between young female and male animals. Old age was associated with impaired central thyroid function in both genders, albeit to a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…In line with these results, there are other studies that show this plant has decreasing effect on the levels of T3 and T4 (9,23). Further investigation indicated that basil leaf extract reduces serum concentrations of T4 (33). Another study found that Betel leaf extract in the lowest dose increases concentrations of T3 but increases concentration of T4 and decreases T3 concentration at higher doses (34).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In line with these results, there are other studies that show this plant has decreasing effect on the levels of T3 and T4 (9,23). Further investigation indicated that basil leaf extract reduces serum concentrations of T4 (33). Another study found that Betel leaf extract in the lowest dose increases concentrations of T3 but increases concentration of T4 and decreases T3 concentration at higher doses (34).…”
Section: Discussionsupporting
confidence: 67%
“…However, there are other studies that show thyroid hormone levels decrease during chronic immobilization stress (7,30). Other studies also argue that chronic immobilization stress decreases plasma levels of TSH and hypothalamic TRH mRNA levels in young rats (32,33). In justifying the lack of effect of chronic immobilization stress on levels of hormones T3, T4 and TSH, adaptation of rats with this stress (13) may fail in changing the activity of thyroid gland during the implementation of this type of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Within s-variant females, dominant females had higher levels than subordinate animals. Thyroid hormones are reduced by hypercortisolism associated with chronic disease [75] as well as restraint stress [76] and food restriction [77,78], effects that may be mediated through a reduction in hypothalamic TRH expression. However, other data indicate this decrease induced by food restriction [47] and stress [48] may occur independent of changes in TRH expression.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, differentiation between primary (or direct) immunotoxic effects and secondary indirect (or stress-related) effects in routine toxicity studies can be challenging Cizza et al 1996;Dominguez-Gerpe and Rey-Mendez 1998). Nevertheless, the morphology of thymus and spleen are an important part of the data set used for the weight-of-evidence approach for evaluating potential stress-related changes.…”
Section: Physiological Organization Of the Immune Systemmentioning
confidence: 99%